Effect of pre-slaughter stunning on the death of the poultry and myofiber apoptosis - Shahdan, Intan Azura; Rahman, Mohammad Tariqur (Universiti Putra Malaysia, 2014)
The effectiveness of poultry stunning in producing swift slaughtering was analysed in response to the time needed for the chickens to become insensible upon neck cutting (Td) and the induction of myofiber apoptosis. In total, 49 chicken broilers (BW of 2.17 ± .24 kg) were sacrificed with pre-slaughter stunning, using a constant voltage stunner where the electric current varied between 7.2 to 124.3 mA, and without stunning. The electric current applied during stunning was found to have no effect on Td. Number of apoptotic myonuclei did not vary among stunned and unstunned meat. Apoptosis inducing factor (AIF) and caspase 3 expressions were also not detected in the meat samples of both stunned and unstunned groups at 1 d postmortem. Since the slaughtering process and stunning are associated with stress, the expression of 70 kDa-heat shock protein (Hsp70) was investigated. Moreover Hsp70 is also an inhibitor of apoptosis, by preventing the activation of AIF and apoptosome which stimulates caspase 3 activation. However, expression of Hsp70 was not induced in both stunned groups and unstunned groups. Together, this study found that poultry stunning does not affect Td and myofiber apoptosis.